Book of Abstracts: Regional Knowledge Forum on Drought: Earth Observation and Climate Services for Food Security and Agricultural Decision Making in South Asia and Southeast Asia, Kathmandu, Nepal, 8-10 October 2018 - Qamer, Faisal M.; Matin, Mir; Bajracharya, Birendra; Ellenburg, Walter Lee (Quality Printers (Pvt.) Ltd., 2019)
Asia has some of the highest peaks in the world as well as several low-lying plains and coastal areas. River basins in Asia – such as the Ganges-Brahmaputra, Indus, Mekong, and Yangtze –provide water that sustains agriculture and livelihoods in the region. Agriculture in this region accounts for two-thirds of the global agricultural gross domestic product (GDP).